ENGLISH TRAINING USING MACROMEDIA FLASH IN ENGLISH LEARNING FOR PAUD TEACHERS IN SENGKANG - Ahmad Munawir; Syahrun Adzim (Jurnal Abdimas Indonesia, 2021)
Learning English and introducing technology to children at a young age is becoming increasingly important in order to meet the demands of an era in which everything is now done in English and is based on technology. To do this, people resources are required who are fluent in two languages: English and technology, both of which are currently unavailable. This is due to a lack of understanding and mastery of technology-based English, which is one of them. The Community Service team of IAI As'adiyah held activities with practical methods related learning English based on macromedia flash based on the previous Community Service program carried out by FTK IAI As'adiyah Sengkang academics, which included training on the use of word and excel. It is envisaged that as a result of this project, PAUD teachers in the Sengkang City area will have more abilities and knowledge in technology-based English education, particularly employing macromedia flash.